SAT0493 Plasma levels of hsp90 are increased in interstitial lung disease and skin fibrosis in patients with systemic sclerosis. (12th June 2018) - Storkanova, H.; Oreska, S.; Spiritovic, M.; Hermankova, B.; Pavelka, K.; Vencovsky, J.; Distler, J.H.; Senolt, L.; Becvar, R.; Tomcik, M.
Abstract : Background: Our previous study demonstrated that Heat shock protein 90 (Hsp90) is overexpressed in the skin of patients with systemic sclerosis (SSc), in cultured SSc fibroblasts and preclinical models of SSc in a TGF-β dependent manner. We showed that Hsp90 is a regulator of TGF-β signalling and its inhibition prevents the stimulatory effects of TGF-β on collagen synthesis and dermal fibrosis in three preclinical models of SSc 1 . Objectives: The aim of this study was to evaluate Hsp90 in the circulation of SSc patients and characterise its potential association with skin changes and SSc-related features. Methods: A total of 91 patients (78 females; mean age 52.7; disease duration 6.0 years; diffuse cutaneous (dc)SSc/limited cutaneous (lc)SSc=38/53) who met the ACR/EULAR 2013 classification criteria for SSc and 85 age-/sex- matched healthy individuals were included. Plasma Hsp90 was measured by ELISA (eBioscience, Vienna, Austria). Data are presented as median (IQR, 25.–75. percentile). Results: Plasma Hsp90 levels were increased in SSc patients compared to healthy controls [12.5 (9.6–17.9) vs. 9.9 (7.9–12.6) ng/mL, p=0.001], but no difference between lcSSc and dcSSc was detected [13.1 (9.4–18.1) vs. 11.5 (9.5–17.5) ng/mL, p=0.316]. Hsp90 levels in all patients positively correlated with CRP (r=0.313, p=0.006). Furthermore, Hsp90 was increased in patients with interstitial lung disease (ILD) compared to those without ILD [12.8 (10.2–17.9) vs. 10.3 (8.6–16.6) ng/mL, p=0.045] and was negatively associated with functional parameters of ILD: FVC (r=−0.299, p=0.011), FEV1 (r=−0.256, p=0.031), DLCO (r=−0.303, p=0.009) and SpO2 (r=−0.317, p=0.038). In addition, only in patients with dcSSc, Hsp90 levels positively correlated with the mRSS (r=0.437, p=0.006). Hsp90 concentrations were not significantly affected by other main clinical parameters of SSc. Conclusions: We demonstrated higher plasma levels of Hsp90 in SSc patients compared to healthy controls. Concentrations of extracellular Hsp90 increase with higher inflammatory activity, with deteriorated lung functions in ILD and also with the extent and severity of the skin involvement in patients with diffuse cutaneous SSc. These data further highlight the role of Hsp90 as a significant regulator of fibroblast activation and tissue fibrosis in SSc. Reference: [1] Tomcik M, et al. Ann Rheum Dis2014;73(6):1215–22. Acknowledgements: Supported by AZV – 16–33542A and SVV – 2 60 373. Disclosure of Interest: None declared